Breakthrough Technologies of Financing Pensions Based on the Supply Chain Strategy in the Russian Federation - Evgeniy Vyacheslavovich Kostyrin; Evgeniy Vasilevich Sokolov; Valentina Vladimirovna Zozulya (International Journal of Supply Chain Management, 2019)
In this paper, the latest technologies of the insurance and funded section of old-age pension financing in the Russian Federation are discussed. For this purpose the supply chain strategies and new technologies effects were considered on the economic performance of companies. The modelling of the funded section of the pension for people with different incomes has been implemented. The advantages of new technology in comparison to the existing procedure of old-age pension financing were presented.